B40 health micro takaful’s working framework in Malaysia - Fauzilah, Salleh; Ahmad Husni, Hamzah; Nik Mohd Norfadzilah, Nik Mohd Rashid (2020)
This study aimed to explore the Health Micro Takaful (HMT) framework for the low-income (B40) communities in Malaysia. A focus group discussion that involved eight participants from various agencies related to the Takaful industry was conducted to determine the underlying basis of the HMT framework with the Central Bank of Malaysia as the regulator. The discussion revealed on the basic protection on diseases, monthly contribution and the implementation for Health Micro Takaful (HMT). With that, the B40 Micro Health Takaful (B40HMT©) framework for the B40 communities in Malaysia was presented in this study.